농촌 청소년의 다문화수용성 영향요인 구조분석 - 장연진; Yeon Jin Jang; 구혜영; Hye Young Koo (청소년복지연구, 2013)
본 연구의 목적은 개인, 가족, 학교 요인이 농촌 청소년의 다문화수용성에 미치는 영향을 알아보고, 이러한 영향관계에 다문화 미디어능력이 어떤 매개효과를 보이는지를 살펴보고자 하는 것이다. 이를 위해 자기효능감, 부모의 다문화 양육태도, 학교의 다문화 교육경험을 독립변수로, 다문화 미디어능력을 매개변수로 하여 구조방정식 모형 분석을 실시하였다. 농촌 소재 중·고등학교에 재학 중인 청소년 469명을 대상으로 분석한 결과, 자기효능감, 부모의 다문화 양육태도, 학교의 다문화 교육경험은 모두 다문화수용성에 유의미한 영향을 미치는 것으로 나타났으며, 다문화 미디어능력도 다문화수용성에 직접적인 영향을 미쳤다. 다문화 미디어능력의 매개효과는 통계적으로 유의미하지 않았으나, 부모의 다문화 양육태도가 다문화 미디어능력에 유의미한 영향을 미치는 것으로 확인되었다. 이러한 연구 결과를 토대로, 농촌 청소년의 다문화수용성향상을 위해서는 청소년 개인의 자기효능감 증진과 함께 부모의 양육태도에 대한 지도와 학교에서의 다문화 교육경험이 종합적으로 제공되어야 하며, 다문화 관련 미디어를 비판적으로 이해하는 능력을 배양해야 한다는 실천적 방안을 제시하였다. The purpose of this article is to study how personal, family and school factors relate to rural adolescents` multicultural acceptability and to investigate the effect of media interpreting ability as mediating factor to this relationship. To achieve this purpose, this study conducted a structural equation modeling analysis using self-efficiency, parenting attitude to multiculture and multicultural learning experiences in school as independent variables. We surveyed 480 adolescents who are in middle and high schools in rural area and used 469 answers for the analysis. The findings of this study are as follows. Self-efficiency, parenting attitude to multiculture, multicultural experiences in school have a significant effect on rural adolescents` multicultural acceptability. Media interpreting ability about multicultural contents also directly affects on multicultural acceptability while it does not have a significant mediating effect on relationship between other factors and multicultural acceptability. This result means it is necessary to provide a comprehensive service for their families and schools as well as themselves in order to increase rural adolescents` multicultural acceptability. Moreover, parents` guidance is important how their children perceive and accept multicultural contents of public media.